Eco-epidemiology of snakebite in Colombia : understanding causes of envenomation in rural population (2020)
"Snakebite is the most neglected of the neglected tropical diseases. Its burden is higher than other diseases in this category, and its data underestimate total burden. This fact reduces the availability for treatment (Antivenom, which decreases drastically lethality and morbidity), so it is crucial to optimize resources and to develop strategies to prevent and control this disease. In this thesis, field work framework and spatio temporal epidemiological models are designed to enhance the empowerment by communities in snakebite management, and tools s that estimate and monitor snakebite incidence were generated, which can be further used to test interventions and to optimize antivenom distribution."